Tourism Management Policy: Division of Makassar City Culinary Area - Lily Diana Fitri Hasan; Muhammad Musawantoro; Faisal Akbar Zaenal (Publik : (Jurnal Ilmu Administrasi), 2021)
Tourism development has a significant role in the development of economic, social, cultural, environmental, political and security aspects. The purpose of this study was to determine the distribution of the culinary area of Makassar City. The development of the tourism sector and its supports has an important meaning in national integration. Infrastructure not only serves to bind the geography of the archipelago, but also guides the birth of participation, efficiency and welfare This study uses a qualitative method. The results of this study indicate that the division of the culinary area in the city of Makassar is divided into 3 parts of the culinary area, namely Datu Museng Makassar City, Culinary Area of  Perintis Kemerdekaan Street and Culinary Area of  Sultan Alauddin Street. These three areas have their respective culinary icons. The culinary area of Datu Museng, Makassar, has a variety of culinary delights such as seafood, epe bananas, konro, otak-otak-pallu butung, pallu basa and others. While in the culinary area, the pioneering street of independence, the culinary icon is Mie Titi. Next, the culinary area of Jalan Sultan Alauddin icon is Coto Alauddin. Makassar's traditional culinary potential has a very big opportunity to develop, especially if it is associated with tourism which triggers interest in visits, regional income and the community. With an effective regional division, culinary will support the economy in Makassar City.